Consensus to identify the dangerous drugs risks in hospital pharmacy services - María Ángeles Bernabeu-Martínez; Pedro García-Salom; Amparo Burgos-San José; Andrés Navarro-Ruiz; Javier Sanz-Valero; Carmina Wanden-Berghe (Farmacia Hospitalaria)
Objective: To identify the hazards and define the theoretical occupational risks arising from the process of handling hazard drugs in hospital pharmacy services on the basis of expert consensus. Method: An expert consensus was conducted (nominal group and documentary techniques) using a mixed method of two face-to-face rounds (meeting of participants and approval of proposals) and three masked rounds (individualized review). The analysis was applied to the field of hospital pharmacy. The stages of the process were designed using the standardized graphical Business Process Model and Notation. Results: A specific flowchart was obtained for the management and traceability of hazardous drugs. All general process phases were characterized. A management chart included operations addressing the reception and storage, compounding, conservation, and dispensation of hazardous drugs in hospital pharmacy services. This chart provides a description of the chemical hazards and exposure routes. Conclusions: The hazardous drug process should be integrated in a standard management system to improve the safety of patients and healthcare professionals. Efficiency can maximized and procedural incidents minimized, thereby ensuring the quality and the safety of hazardous drugs handling in hospital pharmacy services. Once hazards are identified, risk assessment should be implemented using a systematic and preventative methodology to minimize the risk and severity of any adverse event.